Description of a new species of Poeciloxestia Lane from Venezuela (Coleoptera, Cerambycidae) - Haller, Pierre; Santos-Silva, Antonio (Zootaxa, 2023)
A new species, Poeciloxestia nitida sp. nov., is described from Venezuela. The alternative of couplet in two previous keys, in which the new species can be included, is commented.